ON THE ADVANTAGES OF PHOTOMETRIC OBSERVATIONS OF THE GEOSTATIONARYSATELLITES AT SMALL PHASE ANGLES - Sukhov, P. P.; Karpenko, G. F.; Sukhov, K. P.; Epishev, V. P.; Motrunych, I. I.; Kudzej, I.; Dubovsky, P. A. (Одеські астрономічні публікації, 2014)
As a rule, to determine photometric and dynamic characteristics of geostationary satellites required for their identification, long-lasting (from a half of the yearto one year) photometricobservations are needed at GSS different positions relative to the observer. The authors suggest conducting photometric measurements of GSS when they enter and exit the Earth's shadow near equinoxes. On these dates the GSS brightness increases by several magnitudes, so the use of telescopes with a mirror diameter of 50-70 cmcan be effective. For shorter periods it is possible to get more information about the reflective properties of the object than during long-term observations at large phase angles. Several examples of photometric and dynamic characteristics of several GSS obtained near equinoxesare presented here.